INSTRUMEN PENILAIAN AFEKTIF BERBASIS PROFIL PELAJAR PANCASILA - Muhamad Raghib Asfihani; Irfan Fathina; Fitri Hilmiyati; Enung Nugraha (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to develop and describe an affective assessment instrument based on the dimensions of the Pancasila Student Profile. This research employed a library research method by analyzing various literature sources related to affective assessment, learning evaluation, and the implementation of the Pancasila Student Profile within the Merdeka Curriculum. The results indicate that the affective assessment instrument can be developed by referring to six main dimensions of the Pancasila Student Profile: faith and devotion to God Almighty with noble character, independence, mutual cooperation, global diversity, critical reasoning, and creativity. Each dimension can be measured through behavioral indicators relevant to students’ attitudes during the learning process. The use of this instrument is expected to assist teachers in objectively and systematically assessing students’ character development in accordance with Pancasila values